Estrategias de comunicación digital y su incidencia en el posicionamiento de la gestión institucional del gobierno autónomo descentralizado de la parroquia rural la Esperanza, año 2023 - Palate Mayorga, Katherine Gisella (2023)
The objective of this research is to analyze digital communication strategies and their impact on the positioning of the institutional management of the Decentralized Autonomous Government of the rural parish of La Esperanza. For data collection, explanatory, descriptive, and documentary types of research were used, as well as inductive, deductive, and statistical methods. In-depth interviews were conducted with the president of the Decentralized Autonomous Government of the rural parish of La Esperanza, the Director of Public Relations of the Municipality of Quevedo canton, and surveys with the inhabitants of the parish. The results obtained through the studies carried out showed that, despite having digital communication strategies to provide information on the services they perform, there is a low positioning of the image of the institutional management of the GAD de la Esperanza, derived from scarce technological equipment and the absence of specialized technicians, which brings with it social networks and institutional websites that are barely active; and, consequently, little viewed, which implies a poorly informed community. It is evident that the organization faces challenges in its digital communication, institutional positioning and citizen participation. Therefore, it needs to improve the impact on digital platforms, as well as increase awareness of the GAD among citizens and improve the perception of transparency and citizen participation.